تأثير معلومات سلسلة القيمة على جودة تقارير األداء المحاسبية دراسة حالة: بالتطبيق على مصرف الوحدة الليبي - بوبكر خالد معيوف خالد, (Scientific Journal of University of Benghazi, 2021)
The current study aims mainly to measure the quality of performance reports and to test the influence of value chain information on the quality of these reports. This is through a case study applied on Wahda Bank and all its branches in Libya. The data in the financial reports were analyzed during the period from 2008 to 2013 as well as to personal interviews with decision-makers in Wahda Bank. The results show that the bank’s external reports do not contain sectoral information, as they do not contain detailed information and separated from the various branches of the bank. Thus there is a need to improve the quality of accounting reports for performance assessment purposes. There are also statistical impact of value chain information on the quality of accounting performance reports, as it shows the ability of value chain accounting to provide profit information for each activity in detail. It also improves profits and makes management judgments more accurate and objective.